2019
DOI: 10.17216/limnofish.450722
|View full text |Cite
|
Sign up to set email alerts
|

Yağlidere Çayı (Giresun)’nın Bakteriyolojik Kirlilik Düzeyinin Belirlenmesi

Abstract: The aim of this study is to investigate the levels of bacteriological water quality and pollution in Yağlıdere Stream, Giresun, Turkey. For this purpose, surface water and sediment samples were collected monthly, from five stations between June 2013 and May 2014. A bacteriological assessment of water and sediment samples with a 22 °C to 37 °C temperature range, including total coliform bacteria (TC), fecal coliform bacteria (FC), fecal streptococcus (FS), and Escherichia coli were done. Analysis was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…Our another a study performed for different locations at same time in Kilis observed fecal streptococ contamination as 11 EMS/100 mL (Mercimek Takci and Toplar 2023). Although our fecal coliform contamination rates were lower than those shown by Yalım et al (2020) and Akkan et al (2019), our study clearly emphasized the discharge of household and industrial wastewater systems into the surface water without control.…”
Section: Resultscontrasting
confidence: 88%
“…Our another a study performed for different locations at same time in Kilis observed fecal streptococ contamination as 11 EMS/100 mL (Mercimek Takci and Toplar 2023). Although our fecal coliform contamination rates were lower than those shown by Yalım et al (2020) and Akkan et al (2019), our study clearly emphasized the discharge of household and industrial wastewater systems into the surface water without control.…”
Section: Resultscontrasting
confidence: 88%
“…Aydın (2017) reported that percentages of TC, FC, EC and FS in the sixty surface water samples collected from Boğacık Creek were 98.33%, 91.67%, 83.33% and 96.67% respectively. In a similar study conducted in Yağlıdere Creek, the quality variables were detected as 45% for TC, as 71.66% for FC and 56.66% for FS (Akkan et al, 2019). In addition, the researchers pointed out that E. coli was present in the samples collected at any time of the year and the bacteriological flora was damaged.…”
Section: Resultsmentioning
confidence: 88%
“…Total coliform levels in Karacaoren I Dam Lake were detected to range from 500 to 100.000 CFU/100 mL and the presence of fecal coliform was also noted [24]. Akkan et al ( 2019) reported high fecal coliform pollution (71.66)% in surface water bodies collected from Yaglıdere Stream [25].…”
Section: Resultsmentioning
confidence: 98%